Case Report: A Novel Solution to Penile Zipper Injury—The Needle Holder - Philip A. McCann (The Scientific World Journal)
Penile injuries are relatively uncommon[1]. The crush injury mediated by entrapment of the skin between the teeth and fastener of a zipper mechanism has been described[2,3]. It is seen more commonly in uncircumcised children than adults[4]. A number of treatment methods have been mentioned in the literature[5,6]. An adult case presentation and novel method of management using two small needle holders is illustrated.